Pine needle litter acts as habitat but not as food source for stream invertebrates - Márquez, Javier Andrés (2017)
Small streams are ruled by the influence that riparian vegetation has on food webs since it regulates the entry of organic matter and sunlight. The plantation of perennial tree species along banks of grassland streams results in heavy shading of stream bottoms and large inputs of coarse organic matter. In this study, we experimentally analyzed the taxonomic and trophic structure of invertebrate assemblages colonizing pine needles and plastic filaments (mimicking the physical structure of needle accumulations) placed in one afforested and one natural grassland stream from the mountainous region of central Argentina. We studied these two experimental substrates to infer if pine leaves were colonized by invertebrates as food resource or only as a substratum for support and refuge. Coarse mesh litter bags were used to simulate large litter accumulations and four bags of each treatment were randomly removed after 46, 89, and 158 days of exposure. Our study showed that taxonomic and trophic composition of invertebrate assemblages colonizing needles and plastic filaments were mostly similar suggesting that needles constitute mainly a stable habitat but not a trophic subsidy. Richness, diversity, and evenness were lower in assemblages of the afforested stream and differences in taxonomic and trophic structure were also found between afforested and natural grassland streams. We conclude that environmental changes associated to afforestation modified invertebrate assemblages colonizing litter but in the same way for needles and plastic filaments since no evidence was found for supporting that the organic nature of needles makes this substrate different from plastic filaments for invertebrates. Therefore, needles would not be being used as a food resource. Our study highlights the importance of preserving riparian zones mostly unaltered to maintain natural aquatic communities when implementing afforestation programes in grassland landscapes.